IMPLEMENTASI KEBIJAKAN PELIMPAHAN SEBAGIAN URUSAN PEMERINTAHAN DAERAH NON-PERIZINAN KEPADA CAMAT DI KECAMATAN NGANJUK - Nurul Hudha Pribadi; Imam Fachruddin; Teguh Pramono; Fendy Artha Prissando (JURNAL BORNEO AKCAYA, 2023)
This research was conducted to describe and analyze the implementation of Nganjuk Regent Regulation No. 19/2020 on the Delegation of Regional Government Affairs Without Certain Permits to the Regent in Nganjuk Regency. This research is qualitative with a case study approach that involves observation and interviews to collect data. This research uses Edward III's Implementation theory which includes communication, resources, disposition, and bureaucratic structure. The results of the study showed that the implementation of the Nganjuk Regent Regulation on the Delegation of Regional Government Affairs of Certain Non-Permits to the Regent has not been effective. Action is good but still not optimal because the participants who attended the socialization were not leaders but staff, so the delivery was incomplete to the sub-district head. Clear technical guidelines are not yet available, and budget needs analysis is still lacking. Regarding human resources, employees in Nganjuk Regency assessed that the understanding of other civil servants was inadequate due to incomplete socialization among employees. Regarding the budget, Nganjuk district cannot handle all activities related to the delegation of authority in the district. Implementation disposition is good, but the guidelines from the supervisory authority apparatus are still unclear. Regarding the bureaucratic structure, Nganjuk Regency already has a clear and measurable Standard Operating Procedure (SOP) in carrying out its duties and is well fragmented. This shows that implementation in Nganjuk District is going well.